Present status and economic benefit of integrated fish farming system in Noakhali region, Bangladesh (Asian Journal of Medical and Biological Research, 2020)
The present study investigated to know the current status and assessment of the economic benefit of twenty-five integrated fish farms in Noakhali region of Bangladesh. Qualitative and quantitative research data were collected between November 2018 to July 2019 through farm visit, focus group discussion and questionnaire interview. This total farming system covers a total 111.27 hectares of landmass where 78.51 hectares were used for fish production and 32.76 hectares for other production. Six major categories of integration were found, namely fish-poultry-livestock-horticulture, fish-poultry-horticulture, fish-livestock-horticulture, fish-horticulture, fish-poultry and fish-livestock integration. There are 21 fish species, 4 types of reared poultry and 3 types of reared livestock and a variety of fruits and vegetables were cultivated throughout the year. An increasing trend of integration was found in the study area. Total fish production from those 25 integrated farms was 326.4 tons/year, and the production value was BDT 43.37M approximately. Average production of fish, horticulture and poultry were 4.54, 13.96 and 1201.79 tons/ha/year. Total investment in 25 different integrated fish farms was about BDT 185.63M while total return was about BDT 227.85M. The benefit of an integrated farming system was BDT 0.38 M/ha/year. The wastes from livestock and poultry directly or indirectly used as fertilizer in the pond and horticulture farming system. A few farms convert this bio-waste as electrical energy through biogas plants to meet up farm’s electricity demand. With the help of proper guideline, technical and financial support the production of these integration systems could be boosted up. It will play a remarkable positive impact on the total economy of the country.Asian J. Med. Biol. Res. September 2020, 6(3): 525-529